Evaluation of Scales of Tilapia Sp. and Sciaenops ocellatus as Low Cost and Green Adsorbent for fluoride Removal From Water - Nkansah, Marian Asantewah; Dua, Asare Boateng; Aryee, Gabriel Adjei; Adusei-Gyamfi, Junias (Frontiers in Chemistry, 2022)
Water containing more than 1.5 mg/L of fluoride is considered toxic as it causes dental, kidney, and other health problems. With the purpose of helping alleviate these problems by exploring a treatment method for fluoride contamination, this study was to assess the suitability of scales of Tilapia Sp. and Sciaenops ocellatus as a cheaper source of adsorbent for the removal of fluoride from drinking water. The samples which were obtained from the Lapaz Market in Accra, Ghana, underwent treatment to eliminate any impurities. They were then ground into powder and treated with aluminum hydroxide [Al(OH)3]. The treated samples were used for the removal of fluoride from spiked solutions prepared in the laboratory. Batch adsorption was performed by varying parameters such as adsorbent dose (1–8 g/L), initial concentration (2 mg/L to 10 mg/L), and contact time (30–300 min) at pH of 7. A one-way ANOVA was used to validate the significance of the defluoridation process with respect to the different experimental conditions. The optimum adsorbent dose, initial concentration, and contact time were found to be 4 g/L, 10 mg/L, and 300 min, respectively. The results revealed that the maximum percentage removal of fluoride was 76% by Tilapia Sp. and 70% by Sciaenops ocellatus at the optimum conditions. This is an indication that both Tilapia Sp. And Sciaenops ocellatus scales are suitable adsorbents for the removal of fluoride from water. The fluoride adsorption kinetics followed the pseudo-second-order model, and the adsorption isotherm fitted the Freundlich Isotherm model better than the Langmuir Isotherm model. The adsorption intensity and adsorption capacity for Tilapia Sp. were 3.484 L/mg and 0.065 mg/g, and that of Sciaenops ocellatus 3.195 L/mg and 0.045 mg/g respectively.